2012
DOI: 10.1155/2012/705309
|View full text |Cite
|
Sign up to set email alerts
|

Return to Full Functioning after Graded Exercise Assessment and Progressive Exercise Treatment of Postconcussion Syndrome

Abstract: Exercise assessment and aerobic exercise training for postconcussion syndrome (PCS) may reduce concussion-related physiological dysfunction and symptoms by restoring autonomic balance and improving cerebral blood flow autoregulation. In a descriptive pilot study of 91 patients referred to a university clinic for treatment of PCS, a subset of 63 patients were contacted by telephone for assessment of symptoms and return to full daily functioning. Those who experienced symptoms during a graded exercise treadmill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 27 publications
2
80
0
Order By: Relevance
“…This perspective is also supported by the NATA position statement. 2 In our center, we have demonstrated that the BCTT can reveal physiological dysfunction in patients with concussion, 29,30,55,60 differentiate concussion from other diagnoses (eg, cervical injury, depression, migraines), 79,92 and quantify the clinical severity and exercise capacity of concussed patients. 62 Based on the Balke cardiac protocol, the test begins at a speed of 3.2 to 3.6 mph (5.2-5.8 kph, depending on the patient's age and height) at 0% incline.…”
Section: Active Treatment For the Athlete With Prolonged Recovery Submentioning
confidence: 99%
See 1 more Smart Citation
“…This perspective is also supported by the NATA position statement. 2 In our center, we have demonstrated that the BCTT can reveal physiological dysfunction in patients with concussion, 29,30,55,60 differentiate concussion from other diagnoses (eg, cervical injury, depression, migraines), 79,92 and quantify the clinical severity and exercise capacity of concussed patients. 62 Based on the Balke cardiac protocol, the test begins at a speed of 3.2 to 3.6 mph (5.2-5.8 kph, depending on the patient's age and height) at 0% incline.…”
Section: Active Treatment For the Athlete With Prolonged Recovery Submentioning
confidence: 99%
“…Our nonrandomized studies showed that in PCS patients, individualized subthreshold aerobic exercise treatment improved symptoms, fitness, and autonomic function during exercise, 60 and when compared with no intervention, the rate of safe recovery and restoring function (sport and work) improved. 60,92 Investigators 94 in a recent study used a standard cycle-ergometer protocol (the McMaster All-Out Progressive Continuous Cycling Test) in 54 youths (age range ¼ 8.5-18.3 years) with PCS (mean symptom duration ¼ 6.3 months). A total of 63% of participants had symptoms during exertion; however, the number and severity of symptoms improved significantly over the ensuing 24 hours in most patients.…”
Section: Active Treatment For the Athlete With Prolonged Recovery Submentioning
confidence: 99%
“…Leddy et al have played a major role in investigating exercise in patients with PCS [24,25,[89][90][91]93,[99][100][101][102][103]. They demonstrated the safety and efficacy of a graduated treadmill exercise test in patients with PCS.…”
Section: Re-regulation Of Ans and CDmentioning
confidence: 99%
“…As previously mentioned, Leddy et al [24,25,[89][90][91]93,[99][100][101][102][103] have played major roles in investigating aerobic exercise in patients with PCS. One study investigated the use of sub-symptomatic threshold aerobic exercise in normalizing some of the physiologic disturbances seen in PCS, particularly BP, minute ventilation (VE), PETCO 2 and CBF velocity (CBFV) measured by transcranial Doppler [101].…”
Section: Restoration Of Cvrmentioning
confidence: 99%
See 1 more Smart Citation